On the Frequency of Price Overreactions - Guglielmo Maria Caporale; Alex Plastun (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper explores the frequency of price overreactions in the US stock market by focusing on the Dow Jones Industrial Index over the period 1990-2017. It uses two different methods (static and dynamic) to detect overreactions and then carries out various statistical tests (both parametric and non-parametric) including correlation analysis, augmented Dickey–Fuller tests (ADF), Granger causality tests, and regression analysis with dummy variables. The following hypotheses are tested: whether or not the frequency of overreactions varies over time (H1), is informative about crises (H2) and/or price movements (H3), and exhibits seasonality (H4). The null cannot be rejected except for H4, i.e. no seasonality is found. On the whole it appears that the frequency of overreactions can provide useful information about market developments and for designing trading strategies.
Keywords: G12; G17; C63; 330; stock markets; anomalies; overreactions; abnormal returns; VIX; frequency of overreactions